FOOD PHOTOGRAPHY PADA IKLAN DI INSTAGRAM - Halim, Bobby; Yulius, Yosef (Besaung : Jurnal Seni Desain dan Budaya, 2021)
In an advertisement, sometimes there is a meaning that is not straightforwardly presented. Every product advertisement that uses the product is inseparable from the camera point of view. FOOD PHOTOGRAPHY ON ADVERTISING IN INSTAGRAM examines the relationship between camera placement (angle) in influencing the message conveyed by a product advertisement and how photography is used as visual rhetoric. The study was conducted qualitatively with a film semiotic analysis approach. Data on FOOD PHOTOGRAPHY ON ADVERTISING IN INSTAGRAM is grouped with only 1 structure, namely Visual Structure. It was analyzed diachronic using the signifier and signified views. The purpose of this research is to find out and describe the meanings contained in food product advertisements on social media, where Instagram is the media chosen as the sample. This study uses several points of view in its study, namely a close point of view (Close Up), a Medium Viewpoint (Medium Close Up), and a flat point of view (flat lay).